Cyclone track variability over Turkey in association with regional climate - (:unkn) unknown (JOHN WILEY & SONS LTD, 2000)
In this study a set of cyclone frequency statistics is developed and the prevailing tracks of cyclones are derived for a region of the world that has not been previously investigated in detail. Analysis reveals that Turkey experiences the effects of five dominant cyclone trajectories. Investigation of the seasonal variability of the cyclone frequencies shows that the highest number of cyclones occurs during winter. The variability of the subtropical jetstream latitude is analysed by multi-variable regression involving cyclone numbers, the numbers of occurrences of the Mediterranean Persistence High Pressure (MPHP), which is an extension of the Azore High Pressure and their periods. This analysis revealed that the most important factor among the three factors chosen is the number of observed blocking cases over Turkey. Although the northern parts of Turkey are accepted as having a transitional type climate between the Mediterranean and temperate regions, our results showed that they are more influenced by cyclones of Mediterranean origin. Copyright (C) 2000 Royal Meteorological Society.
Keywords: cyclone track; regional climate; Turkey; variability; EUROPE; PATTERNS